Selecting Presuppositions in Conditional Clauses. Results from a Psycholinguistic Experiment - Domaneschi, Filippo; Carrea, Elena; Penco, Carlo; Greco, Alberto (Frontiers in Psychology, 2016)
In this paper, we propose an experiment concerning presupposition selection in conditional sentences containing a presupposition trigger in the consequent. Many theories claim that sentences like if p, qq'—where q is the presupposition of the assertive component q'—have unconditional presuppositions, namely, they simply project q. Other theories suggest that these kinds of conditional sentences project conditional presuppositions of the form if p, q. Data collected suggest two results: (i) in accordance with other experiments (by Romoli), dependence between the presupposition q and the antecedent p favors the selection of a conditional presupposition if p, q. (ii) presupposition selection in conditional sentences with a trigger in the consequent is affected by speakers' cognitive load: if speakers are highly cognitive loaded, then they are less disposed to select a conditional presupposition. We conclude by arguing that cognitive load represents a key factor for the analysis of linguistic and philosophical theories of context.